Median Nerve Entrapment after Supracondylar Humeral Fracture in a Young Child. (30th October 2019) - Granier, C.; Maury, E.; Coulet, B.; Delpont, M.; Cottalorda, J.; Sleth, C.; Carré, R.; Louahem, D.
Abstract : Median nerve entrapment after supracondylar humeral fracture in children is rare. We report a case of Gartland type III supracondylar humeral fracture complicated by an entrapment of the median nerve following closed reduction and percutaneous pinning in a 5-year-old child. The diagnosis of entrapment was made 14 months post injury following progressive motor and sensory palsy. Resection and end-to-end suture were performed, leading to complete sensory and motor recovery eight months later. This nerve complication is often unnoticed and should be suspected systematically before and after reduction of all displaced supracondylar humeral fracture in children. The indication of resection-suture or nerve graft depends on the entrapment and the delay of the palsy.